(x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106

Simple and best practice solution for (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 equation:


Simplifying
(x + 10)(x + 5) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106

Reorder the terms:
(10 + x)(x + 5) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106

Reorder the terms:
(10 + x)(5 + x) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106

Multiply (10 + x) * (5 + x)
(10(5 + x) + x(5 + x)) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106
((5 * 10 + x * 10) + x(5 + x)) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106
((50 + 10x) + x(5 + x)) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106
(50 + 10x + (5 * x + x * x)) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106
(50 + 10x + (5x + x2)) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106

Combine like terms: 10x + 5x = 15x
(50 + 15x + x2) + (x + -3)(x + 12) + (x + 11)(x + 30) = 106

Reorder the terms:
50 + 15x + x2 + (-3 + x)(x + 12) + (x + 11)(x + 30) = 106

Reorder the terms:
50 + 15x + x2 + (-3 + x)(12 + x) + (x + 11)(x + 30) = 106

Multiply (-3 + x) * (12 + x)
50 + 15x + x2 + (-3(12 + x) + x(12 + x)) + (x + 11)(x + 30) = 106
50 + 15x + x2 + ((12 * -3 + x * -3) + x(12 + x)) + (x + 11)(x + 30) = 106
50 + 15x + x2 + ((-36 + -3x) + x(12 + x)) + (x + 11)(x + 30) = 106
50 + 15x + x2 + (-36 + -3x + (12 * x + x * x)) + (x + 11)(x + 30) = 106
50 + 15x + x2 + (-36 + -3x + (12x + x2)) + (x + 11)(x + 30) = 106

Combine like terms: -3x + 12x = 9x
50 + 15x + x2 + (-36 + 9x + x2) + (x + 11)(x + 30) = 106

Reorder the terms:
50 + 15x + x2 + -36 + 9x + x2 + (11 + x)(x + 30) = 106

Reorder the terms:
50 + 15x + x2 + -36 + 9x + x2 + (11 + x)(30 + x) = 106

Multiply (11 + x) * (30 + x)
50 + 15x + x2 + -36 + 9x + x2 + (11(30 + x) + x(30 + x)) = 106
50 + 15x + x2 + -36 + 9x + x2 + ((30 * 11 + x * 11) + x(30 + x)) = 106
50 + 15x + x2 + -36 + 9x + x2 + ((330 + 11x) + x(30 + x)) = 106
50 + 15x + x2 + -36 + 9x + x2 + (330 + 11x + (30 * x + x * x)) = 106
50 + 15x + x2 + -36 + 9x + x2 + (330 + 11x + (30x + x2)) = 106

Combine like terms: 11x + 30x = 41x
50 + 15x + x2 + -36 + 9x + x2 + (330 + 41x + x2) = 106

Reorder the terms:
50 + -36 + 330 + 15x + 9x + 41x + x2 + x2 + x2 = 106

Combine like terms: 50 + -36 = 14
14 + 330 + 15x + 9x + 41x + x2 + x2 + x2 = 106

Combine like terms: 14 + 330 = 344
344 + 15x + 9x + 41x + x2 + x2 + x2 = 106

Combine like terms: 15x + 9x = 24x
344 + 24x + 41x + x2 + x2 + x2 = 106

Combine like terms: 24x + 41x = 65x
344 + 65x + x2 + x2 + x2 = 106

Combine like terms: x2 + x2 = 2x2
344 + 65x + 2x2 + x2 = 106

Combine like terms: 2x2 + x2 = 3x2
344 + 65x + 3x2 = 106

Solving
344 + 65x + 3x2 = 106

Solving for variable 'x'.

Reorder the terms:
344 + -106 + 65x + 3x2 = 106 + -106

Combine like terms: 344 + -106 = 238
238 + 65x + 3x2 = 106 + -106

Combine like terms: 106 + -106 = 0
238 + 65x + 3x2 = 0

Factor a trinomial.
(17 + x)(14 + 3x) = 0

Subproblem 1

Set the factor '(17 + x)' equal to zero and attempt to solve: Simplifying 17 + x = 0 Solving 17 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-17' to each side of the equation. 17 + -17 + x = 0 + -17 Combine like terms: 17 + -17 = 0 0 + x = 0 + -17 x = 0 + -17 Combine like terms: 0 + -17 = -17 x = -17 Simplifying x = -17

Subproblem 2

Set the factor '(14 + 3x)' equal to zero and attempt to solve: Simplifying 14 + 3x = 0 Solving 14 + 3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 3x = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 3x = 0 + -14 3x = 0 + -14 Combine like terms: 0 + -14 = -14 3x = -14 Divide each side by '3'. x = -4.666666667 Simplifying x = -4.666666667

Solution

x = {-17, -4.666666667}

See similar equations:

| 2x^4=35 | | 1n+9=4n+3 | | -16x^2+240x+20=0 | | 2.5x+2.4=7.8 | | 4m-8+2m=2(3m-4) | | 3x^2-3=2x-1 | | 3n+6=4n+1 | | 5-21=2a | | solvex+0.08(60)=0.20(60+x) | | 3(x+5)=x+3+2x | | Sen(2x)+sen(4x)=0 | | 47.1=29.7-0.2x | | -47(x-11)-34=10-12 | | 2m-28=9m | | 2-7k=-4(k+1)-3 | | 4(x-8)=2x+6-x | | 3z-19=123 | | 2[t-(2t+8)+6]=2(t+2) | | 5x(x+8)+5x(6-x)=9(12+x)-8(7-x) | | 7(-6)(5)= | | 4z^2+3z-1=0 | | 2x^2-3y=32 | | -(z+7)+(5z+1)=5(z+1) | | 5x-19=3x+6 | | 3x(x+3)=24 | | 27x=33 | | 100-50= | | 8cosx-3=0 | | F(-1)=3x^3-5x^2-2x-5 | | 5x-2=125 | | 3x-7i=3(3x-7u) | | 8n+32=4(7n-7) |

Equations solver categories